2023
DOI: 10.1017/s0022215123001743
|View full text |Cite
|
Sign up to set email alerts
|

The mental health of paediatric cochlear implant recipients

Si-Jie Ma,
Si-Xuan Li,
Huan Tan
et al.

Abstract: Objectives. To evaluate the mental health of paediatric cochlear implant users and analyse the relationship between six dimensions (movements, cognitive ability, emotion and will, sociality, living habits and language) and hearing and speech rehabilitation. Methods. Eighty-two cochlear implant users were assessed using the Mental Health Survey Questionnaire. Age at implantation, time of implant use and listening modes were investigated. Categories of Auditory Performance and the Speech Intelligibility Rating S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…7 Mental health seems like a sensible component of this evaluation. This issue has a paper from Lanzhou (China) which examines the mental health of 82 paediatric cochlear implant recipients, 8 as assessed by a mental health survey questionnaire for 3-6-year-old children adapted from a previous US developmental questionnaire. The authors found that children who received implants earlier than others had better mental health scores, which indicated better rehabilitation after surgery.…”
Section: Edward W Fisher and Jonathan Fishmanmentioning
confidence: 99%
“…7 Mental health seems like a sensible component of this evaluation. This issue has a paper from Lanzhou (China) which examines the mental health of 82 paediatric cochlear implant recipients, 8 as assessed by a mental health survey questionnaire for 3-6-year-old children adapted from a previous US developmental questionnaire. The authors found that children who received implants earlier than others had better mental health scores, which indicated better rehabilitation after surgery.…”
Section: Edward W Fisher and Jonathan Fishmanmentioning
confidence: 99%